О нормах произношения в современном английском языке - Анусас, П. (Kalbotyra, 1978)
In the present article an attempt bas been made to analyse some of the major approaches concerning standards of pronunciation. As a result of close and careful study of the problem, many linguists have come to the conclusion that: 1) distinction should be made between norm (standard) and codification; 2) there is no such thing as a general norm, there is a series of norms. It is quite evident that norms in matters of vocabulary and grammar differ from those in pronunciation. The latter should comprise not only the segmental (phonemic) but also the suprasegmental (prosodic) level. The homogeneous type of English pronunciation (RP), generally found in pronouncing dictionaries and text-books on phonetics is actually the result of codification which is used but in a limited number of situations in which people communicate, rather than the norm itself.